Using DNA as a drug-Bioprocessing and delivery strategies - Han, Y.; Liu, S.; Ho, J.; Danquah, Michael; Forde, G. (Elsevier, 2009)
DNA may take a leading role in a future generation of blockbuster therapeutics. DNA has inherent advantages over other biomolecules such as protein, RNA and virus-like particles including safety, production simplicity and higher stability at ambient temperatures. Vaccination is the principal measure for preventing influenza and reducing the impact of pandemics; however, vaccines take up to 8-9 months to produce, and the global production capacity is woefully low. With production times as short as 2 weeks, improved safety and stability, bioprocess engineering developments, and the ability to perform numerous therapeutic roles, DNA has the potential to meet the demands of emerging and existing diseases. DNA is experiencing sharp growths in demand as indicated by its use in gene therapy trials and DNA vaccine related patents. Of particular interest for therapeutic use is plasmid DNA (pDNA), a form of non-genomic DNA that makes use of cellular machinery to express proteins or antigens. The production stages of fermentation and downstream purification are considered in this article. Forward looking approaches to purifying and delivering DNA are reported, including affinity chromatography and nasal inhalation. The place that pDNA may take in the preparation for and protection against pandemics is considered. If DNA therapeutics and vaccines prove to be effective, the ultimate scale of production will be huge which shall require associated bioprocess engineering research and development for purification of this large, unique biomolecule. © 2008 The Institution of Chemical Engineers.